Construction of direct Z-scheme system for enhanced visible light photocatalytic activity based on Zn0.1Cd0.9S/FeWO4 heterojunction. (9th September 2019) - Tang, Yunxiang; Kong, Dezhi; Wang, Xiaotong; Ma, Yuxue; Su, Changhua; Pu, Xipeng; Geng, Yanling
Abstract: A novel direct Z-scheme Zn0.1 Cd0.9 S/FeWO4 (ZCS/FW) photocatalyst was prepared by a facile calcination method. The photocatalytic performance was investigated by photodegradation rhodamine B (RhB) and photocatalytic production hydrogen (H2 ) under visible light irradiation. Compared with the pure ZCS, the ZCS/FW composites show considerably improved photocatalytic activity for degradation RhB and production H2 . Noticeably, the ZCS/FW with 7 wt% of FW exhibits optimal photocatalytic activity with the H2 evolution rate of 34.6 mmol g −1 h −1 and photodegradation of about 98% of RhB solution (10 mg l −1 ) in 60 min. These outstanding photocatalytic performances were found to be ascribed to the formation of direct Z-scheme heterojunction, resulting in effective separation and transfer of photogenerated charge carriers. Moreover, active species trapping experiments further demonstrate the electrons transfer followed Z-scheme system, and the photocatalytic mechanism was proposed.